Aluminum in quartz of the Darasun gold deposit (Eastern Transbaikal region, Russia) - L. T. Rakov; V. Y. Prokofiev; E. A. Minervina; L. D. Zorina (Georesursy, 2024)
Quartz samples taken from the ore veins of the Darasun gold deposit (Eastern Transbaikalia, Russia) were studied using electron paramagnetic resonance (EPR) and laser ablation (LA) methods. The purpose of the research was to clarify the behavior of the Al impurity during quartz crystallization and its subsequent recrystallization. The results of the research were used to determine the genetic informativeness of the Al impurities concentration in ore quartz.A separate study of the regularities of the distribution of Al impurity in the regions of crystalline structure and in the zones of crystal lattice distortions was carried out. In the regions of crystalline structure, the Al impurity concentration NAL was determined by the concentration of paramagnetic Al–O– -centers associated with the presence of substitutional Al3+ ions. The content of the Al impurity in the zones of crystal lattice distortions was judged by the difference between the gross concentrations of aluminum CAl and the values of NAL. It was taken into account that the intensity and direction of the studied processes can be influenced by the temperature of quartz formation and the degree of its recrystallization. The temperature of quartz formation was estimated by the values of Ti impurity concentration, and the degree of recrystallization was estimated by the content of Li impurity CLi in the mineral.It was found that the amount of Al impurity localized in the zones of crystal lattice distortions is an order of magnitude higher than that present in the zones of crystalline structure. It is shown that this phenomenon is explained by the high ability of the zones of crystal lattice distortions to capture of Al impurity during quartz crystallization. The amount of Al impurity trapped by quartz increases sharply with an increase in the temperature of the mineral formation. In areas of regions of crystalline structure, a different picture is observed − impurity capture during crystallization proceeds with low intensity and is not so critically dependent on temperature.It was found that the Al impurity in the considered zones behaves differently during quartz recrystallization. If Al impurity capture continues in the regions of crystalline structure, then Al impurity removal from quartz can occur in the zones of crystal lattice distortions at high CAl values.Based on the data obtained, the areas of use of aluminum impurity contents as a typomorphic feature of ore quartz were determined. The Al impurity concentrations proved to be suitable for use in cases of low ore formation temperatures, and its gross CAl contents have the prospect of wider use. It is noted that a characteristic feature for quartz from high productivity zones is a negative angle of slope of the CAl(CLi) dependence plot.